Health-related quality of life in patients with chronic rhinosinusitis measured by the Vietnamese EQ-5D-5L set value - Hoang, Phuoc Minh; Doan, Thi Thuy Hien; Nguyen, Nhu Nguyen Anh (Tạp chí Y Dược Huế, 2025)
Background: Chronic rhinosinusitis (CRS) is one of the most prevalent chronic conditions, leading to significant health and economic burdens. Health-related quality of life can be reflected by Health Utility Index (HUI). Tools such as the EuroQol-5-Dimensions-5-Levels (EQ-5D-5L) and the Visual Analog Scale (VAS) are widely used to assess HUI in CRS patients. This study aimed to determine the overall HUI of Vietnamese patients with CRS and identify factors influencing it. Materials and Methods: A cross-sectional study was conducted at Hue University of Medicine and Pharmacy Hospital from January 2024 to December 2024. Patients with a diagnosis of primary CRS were recruited. Clinical data and HUI measurements were collected, and regression models were used to predict the HUI of CRS patients. Results: A total of 51 patients were enrolled. The overall HUI, as assessed by EQ-5D-5L and VAS, was 0.75 ± 0.15 and 0.73 ± 0.14, respectively. No significant difference was found between the two methods in measuring HUI. Multivariable linear regression revealed that each unit increase in the 22-item Sinonasal Outcome Test (SNOT-22) score reduced the HUI by 0.003, while each unit increase in the VAS score for overall symptoms resulted in a 0.02 decrease in the HUI. Conclusions: The overall HUI for CRS patients ranged between 0.73 and 0.75. Higher SNOT-22 and VAS for overall symptoms scores were associated with lower HUI, highlighting their negative impact on health utility.